Lesson Effectiveness, Strong and Weak Sides of the Initial Implementation of the Integrated Language Approach - Birova, Jana (Communications - Scientific Letters of the University of Zilina, 2014)
We analyse effectiveness of the French lesson in the initial implementation of the method called integrated language approach at primary school. The article presents the results of the qualitative research methods - indirect observation, interaction analysis and collective observation and content analysis. We summarise also strong and weak sides of the implementation of the method.
Keywords: integrated language approach; FREPA; French; English; effectiveness